The use of tricyclic antidepressants in treatment of migraines: a literary approach (Research, Society and Development, 2023)
The study addresses the significant contribution to the analysis of the pharmacological treatment of migraine, which is a neurovascular disorder consisting of abnormal neuromuscular reactions in genetically vulnerable individuals that can be treated with the use of tricyclic antidepressants, the object of the present study.  The study is an integrative literature review with a qualitative approach. Between November 2022 and March 2023, the bibliographic survey was carried out through the Virtual Health Library (VHL) platform, the consultation of articles in the following databases: BDENF, LILACS and Pubmed. The results indicated the use of tricyclic antidepressants in the treatment of migraines according to the types of crises, considering the potential of pain for their respective pharmacological control. Through the study it was found that the use of tricyclic antidepressants in the treatment of migraines should have judicious use in acute treatment and the elimination of risk factors for headaches, which can clearly and significantly share the pain caused in many patients, but, it can be cited the existence of other drugs has been shown to be effective in the treatment of headaches with antidepressants among others.